THE INSTITUTIONS OF CULTURAL STUDIES - Schleifer, Ronald (Surfaces, 1992)
An account of the disciplinary problematic of cultureal studies. How does a theoretical and analytic enterprise take on an institutional form? Special reference to the establishment of a program in cultural studies at the University of Oklahoma.